Protection of Baby Shamans as Non-Medical Health Workers Reviewed from the Job Creation Law - Anita Fitria (Civiliza Publishing, 2026)
Law Number 36 of 2014 concerning Health Workers stipulates that health workers must have formal education, competence, registration, and practice licenses. This provision causes baby shamans to not be recognized as official health workers, even though they still play a role in public health services based on local wisdom. This study aims to analyze the legal protection of baby shamans as non-medical health workers reviewed from the Job Creation Law. The research uses a qualitative method with a juridical sociological approach through interviews, observations, and documentation studies. The results of the study show that the legal position of baby shamans is still weak juridically, but strong sociologically. Legal protection from the perspective of the Job Creation Law is still normative and not optimal because it has not been supported by technical regulations that regulate legality, work safety, competence, welfare, and partnerships comprehensively. Its implementation also faces regulatory constraints, institutions, policy implementation, socio-cultural, economic, and limited access to information. Therefore, harmonization is needed through the recognition of local wisdom, strengthening partnerships with health workers, drafting more responsive regulations, and sustainable coaching. This study concludes that legal protection for baby shamans is still not optimal, so a more specific, integrated, and sustainable policy is needed.